THE POLITICS OF USING MACKINDER’S GEOPOLITICS: THE EXAMPLE OF UZBEKISTAN - MEGORAN, Nick (CENTRAL ASIA AND THE CAUCASUS, 2005)
As both recent scholarly publications, and colloquia in London, Glasgow and Tashkent demonstrate, there remains considerable interest in the thinking of Halford Mackinder. Two major streams of scholarship can be identified—the study of the application of his theories to international relations, and the investigation of their intellectual provenance. This paper will focus on the second of these concerns, making use in particular of a body of scholarship on Mackinder known as “critical geopolitics,” especially the work of Gearóid Ó Tuathail (Gerard Toal). It will consider what new insights can be gained from the application of this approach to studies of contemporary Central Asia that themselves use Mackinder’s ideas. It asks not, “what does Mackinder’s theory reveal about the world and Central Asia’s place in it?” but “what does Mackinder’s theory reveal about Mackinder” and, crucially, “how have citations of Mackinder’s theory been used to construct contemporary geopolitical narratives about Central Asia?”The first approach to Mackinder takes his Pivot/Heartland theory as a model with predictive capacities that can be tested against the “course of events,” and from which policy recommendations can be derived. Such a method was used principally to analyze the Cold War and was particularly popular with international relations theorists. It has almost entirely relied on limited readings of three of Mackinder’s works, his 1904, 1919, and 1943 iterations of the Heartland thesis.1 It does not connect these to the wider corpus of Mackinder’s writings and attaches minimal importance to his biography. A typical example of this approach is the work of Colin Gray, who argues that Mac-kinder correctly recognized the Heartland as “an enduring geostrategic reality of the first importance,” and that his theory proved accurate in the twentieth century and may well prove so in the twenty-first.2 The second approach, developed by geographers, contextualizes the Heartland thesis in two ways.On the one hand, it locates the three famous “geopolitical” texts in the context of Mackinder’s wider thought and political and professional activities, and was built upon biographies published in the 1980s.3 On the other, it situates Mackinder’s thought in wider contemporary social and political circumstances, such as international diplomacy,4 and debates on British engagement with Central Asia,5 imperial defense policy,6 and military reform.7 Kearns has developed an innovative variation on this technique, contrasting Mackinder’s approach to topics as diverse as imperial economic reform,8 exploration,9 and the purpose of geography,10 with those of close contemporaries. Whilst some of these writers have been hostile to the Mackinder legacy, and others have celebrated it, all have agreed that his three most famous texts cannot be detached from the time and place of their production and the biography and guiding vision of their author.